The study of the Landuse/Landcover change in Sirsa River Basin, Himachal Pradesh Using Remote Sensing Data - Verma, Narender; Dash, Pratik (National Geographical Journal of India, 2022)
Sirsa River Basin, a tributary of Sutlej River that flows through Himachal Pradesh and Punjab has witnessed changes in land use owing to significant growth of population and industrial expansion in Himachal Pradesh. Baddi town in Solan district has emerged as a major industrial hub in the last two decades. In the present study an attempt is made to trace the land use land cover change in the Sirsa river basin during 1989-2009 using Landsat data. Since the ultimate objective of delineating land use land cover was to study its impact on the hydrological characteristics of the study basin (not discussed in the present paper) river basin has been chosen as a unit of study and only the results of land use land cover change at the basin level have been incorporated in this paper. Landsat TM data of 1989 and 2009 and Landsat ETM+ data of 1999 have been used in this study. Supervised classification using maximum likelihood algorithm followed by post classification readjustment of classes through recode function and change detection have been performed in GIS environment. Also an accuracy assessment using Kappa coefficient has been done to assess the accuracy of the results. Significant changes in land use land cover have been observed. While on one hand there has been a significant reduction in area under dense & open forests by 16% each and barren land by 50%, built up area has sporadically increased by a whooping 1500% during period under study. The overall accuracy and kappa coefficients(k) for 2009 image are 85.19% and k= 81.77% whereas for 1989 and 1999 the corresponding values are 61.48 %, k= 52.77 and 62.22 %, k= 53.60.